Simple web controlled home automation system with fault detection / M. N. Ismanto and E. Abbas - M. N., Ismanto; E., Abbas (2017)
This paper reports an ongoing project related to the development of Web Controlled Home Automation System. The system contains three (3) main functional blocks which are (i) webpage to provide Graphical User Interface (GUI), (ii) Controller Bridge consists of Arduino UNO and Arduino Ethernet Shield, and (iii) switching unit as a task executor. The project focuses on creating a simple and easy system to control home appliances using user-friendly GUI which is a website page. There is also a built-in fault detection module. This project has two (2) main tasks. There are (i) building simple system for web controlled home automation system with a system fault feedback reporting, and (ii) developing the system programming and creating user-friendly website page with interesting GUI. The system is connected to the Internet through the Arduino Ethernet Shield using RJ45 cable.